Pathfinder elements for gold exploration in the Hongqigou tectonic zone of the Wulonggou goldfield (Qinghai Province, Western China) - Zhen, Shikun; Sun, Meiqing; Xia, Chulin; Zhang, Wenzhao; Quan, Chang’en; Han, Zhihong; Du, Yu (Frontiers in Earth Science, 2022)
Gold is strongly enriched (up to 12 ppb) in the Hongqigou tectonic zone, which represents a potential metal source for the Wulonggou goldfield. In this study, a suite of 20 elements (Au, Ag, As, B, Ba, Bi, Cd, Co, Cu, Hg, Mn, Mo, Ni, Pb, Sb, Sn, Ti, V, W and Zn) were analyzed on 30 altered rock samples from the tectonic zone. Compared with the average upper crust, these samples are generally enriched in Hg, have comparable Au, Ba and As, and depleted in Ba, Co and W. We suggested that Au, As, Hg, and Ba are the major ore-forming elements. Coupling relationship in multielement variation patterns between the altered rocks (in the tectonic zone) and wallrocks indicates wallrock involvement during the alteration process. Correlation statistical analysis (with SPSS software) on the 20 elements suggests that the elements of Ag, Cu, Pb, Hg, and Cd are closely related, and useful pathfinder elements include As, Sb, Hg, W, Sn, Cu, Ni, Mn and Zn.